The Change Agent's Innovation in Financial Literacy Inclusion in Jakarta - MARIS, Rizal J.; SUNARTO, Sunarto; WIDOWATI, Dewi; NAFIAH, Ariani (PT Keberlanjutan Strategis Indonesia, 2023)
OJK surveys (2019 and 2022) show that the financial literacy index is lower than the financial inclusion index. The fact that the Financial Education Working Group has not carried out communication activities (diffusion) effectively. This study tries to see the innovation of communication activities from the Financial Education Working Group, as an agent of change in communication activities related to financial literacy to the community, so far. The Diffusion Theory of Innovation from Everett M. Rogers (1995) is used to explain the problem. The method using multiple case studies from Yin (2022) is qualitative descriptive. Interviews were conducted in ”snowball” manner to members of the Financial Education Working Group and the data were analyzed through the interactive model Miles & Huberman (2007). The results show that the relative advantage of diffusion innovation exists, but it is not too significant because of the lack of participation. Compatibility diffusion approaches differ from method to method and are only effective when tailored to the target or recipient of the information. In terms of complexity, the diffusion approaches used are relatively easy because they are often used in, such as, seminars, workshops, counseling, or in the use of digital media. These diffusion approaches meet the element of trialability.observability; the diffusion approach used can be observed and results include, the number of participants, the enthusiasm of participants, the number of activities, and others.